Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41598-018-30772-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of platelet lysate as a substitute for FBS in explant and enzymatic isolation methods of human umbilical cord MSCs

Abstract: Mesenchymal stem cells (MSCs) have immense potential for cell-based therapy of acute and chronic pathological conditions. MSC transplantation for cell-based therapy requires a substantial number of cells in the range of 0.5–2.5 × 106 cells/kg body weight of an individual. A prolific source of MSCs followed by in vitro propagation is therefore an absolute prerequisite for clinical applications. Umbilical cord tissue (UCT) is an abundantly available prolific source of MSC that are fetal in nature and have higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 46 publications
2
50
0
Order By: Relevance
“…Unlike in other studies, here ASCs were expanded using human platelet lysate in the culture media, which may have the advantage of avoiding the use of animal‐derived factors. Human platelet lysate is widely used to grow MSCs, and many studies have demonstrated that this confers a degree of safety that is at least equivalent to that offered by fetal bovine serum . Indeed, some studies have suggested that the use of platelet lysate may increase cell yield and shorten the time for ex vivo expansion without epigenetic alterations …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike in other studies, here ASCs were expanded using human platelet lysate in the culture media, which may have the advantage of avoiding the use of animal‐derived factors. Human platelet lysate is widely used to grow MSCs, and many studies have demonstrated that this confers a degree of safety that is at least equivalent to that offered by fetal bovine serum . Indeed, some studies have suggested that the use of platelet lysate may increase cell yield and shorten the time for ex vivo expansion without epigenetic alterations …”
Section: Discussionmentioning
confidence: 99%
“…Human platelet lysate is widely used to grow MSCs, [23][24][25] and many studies have demonstrated that this confers a degree of safety that is at least equivalent to that offered by fetal bovine serum. 26,27 Indeed, some studies have suggested that the use of platelet lysate may increase cell yield and shorten the time for ex vivo expansion without epigenetic alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been highlighted that there is a need to find alternatives to FBS for use as a media supplement for MSC culture, due to the risk of transmitting pathogens that may cause viral infections and bacterial infections, transmission of prions, inflammatory reactions due to contamination with bovine proteins, and ethical issues with collection of animal products [11,12,15,17]. Alternatives have been considered: MSCs have been cultured successfully in autologous [18,19] and non-autologous [20,21] human serum, human platelet lysate [12,17,20], autologous cord blood serum [20,22], and autologous cord blood platelet rich plasma [23,24]. Serum is collected from whole blood after it is left for a specific set time to clot and is then subsequently centrifuged [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet rich plasma is produced when the platelet pellet is re-suspended in the plasma after centrifugation [27,24]. Platelet lysate is produced when the platelet rich plasma is taken through a number of freeze thaw cycles [25,28,29].…”
Section: Introductionmentioning
confidence: 99%